The intellectual powers : a study of human nature - Hacker, P. M. S. (Peter Michael Stephan) (Chichester, West Sussex ; Malden, MA : Wiley/Blackwell, 2013)
The Intellectual Powers is a philosophical investigation into the cognitive and cogitative powers of mankind. It develops a connective analysis of our powers of consciousness, intentionality, mastery of language, knowledge, belief, certainty, sensation, perception, memory, thought, and imagination, by one of Britain's leading philosophers. It is an essential guide and handbook for philosophers, psychologists, and cognitive neuroscientists. The culmination of 45 years of reflection on the philosophy of mind, epistemology, and the nature of the human personNo.
3. The classical causal theory of perception4. The modern causal theory of perception; 9: Memory; 1. Memory as a form of knowledge; 2. The objects of memory; 3. The faculty and its actualities; 4. Forms of memory; 5. Further conceptual links and contrasts; 6. The dialectic of memory I: the Aristotelian legacy; 7. The dialectic of memory II: trace theory; PART II: The Cogitative Powers; 10: Thought and Thinking; 1. Floundering without an overview; 2. The varieties of thinking; 3. Is thinking an activity?; 4. What do we think in?; 5. Thought, language and the language of thought.
Includes index.
Print version record and CIP data provided by publisher.
Keywords: Philosophical anthropology; Philosophy of mind; Thought and thinking; PHILOSOPHY -- Movements -- Humanism; Philosophical anthropology; Philosophy of mind; Thought and thinking; Electronic books; Electronic books